2013
DOI: 10.1007/s11845-013-1033-8
|View full text |Cite
|
Sign up to set email alerts
|

Readability and content of patient information leaflets for endoscopic procedures

Abstract: This study raises significant concerns about the readability and content of current Irish PILs, and it is unlikely that these issues are restricted to leaflets given prior to endoscopy. A standardised approach to developing PILs for common elective procedures, with minimum standards for readability and a uniform approach, based on current Irish legal requirements, to risk disclosure, might be helpful.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 11 publications
3
14
0
Order By: Relevance
“…It is not possible to assess specific components of PILs using standard readability algorithms as the word count for these components is too small. Our study shows similar results to those found by Gargoum et al (2014) in a comparable analysis carried out in the Republic of Ireland. 15 There are limitations to the use of standardised readability and comprehension scores in assessing effectiveness of patient information leaflets.…”
Section: Nhs England's Information Standard Workhop Provides In-supporting
confidence: 92%
See 1 more Smart Citation
“…It is not possible to assess specific components of PILs using standard readability algorithms as the word count for these components is too small. Our study shows similar results to those found by Gargoum et al (2014) in a comparable analysis carried out in the Republic of Ireland. 15 There are limitations to the use of standardised readability and comprehension scores in assessing effectiveness of patient information leaflets.…”
Section: Nhs England's Information Standard Workhop Provides In-supporting
confidence: 92%
“…Our study shows similar results to those found by Gargoum et al (2014) in a comparable analysis carried out in the Republic of Ireland. 15 There are limitations to the use of standardised readability and comprehension scores in assessing effectiveness of patient information leaflets. 16 Multiple factors influence the readability of a document, and not all of these are assessed by the methods used in this analysis.…”
Section: Nhs England's Information Standard Workhop Provides In-supporting
confidence: 92%
“…Provision of information precolonoscopy has been linked to lower anxiety and British Society of Gastroenterology guidelines emphasise the importance of written information preprocedure 35 36. However, studies report variations in amount of information provided for colonoscopy and gastroscopy, and that reading levels often exceed recommended reading age standards 37–39. Our results suggest patients desire different types and amounts of information and different modes of delivery (ie, one size does not fit all).…”
Section: Discussionmentioning
confidence: 72%
“…Multiple studies have demonstrated that patient education resources are too difficult for approximately one-quarter of US adults to read and comprehend (Badarudeen and Sabharwal 2010 ; Mueller et al, 2010 ; Paasche-Orlow et al 2003 ). Because literacy difficulties are prevalent, many Institutional Review Boards recommend that language should be aimed at the 8th grade reading level (Badarudeen and Sabharwal 2010 ; Gargoum and O’Keeffe 2014 ; Simon et al 2012 ). The quantity and complexity of information included in a consent form for WES makes it challenging to meet the 8th grade reading level target (Badarudeen and Sabharwal 2010 ; Gargoum and O’Keeffe 2014 ; Paasche-Orlow et al 2003 ; Simon et al 2012 ).…”
Section: Introductionmentioning
confidence: 99%